HUBUNGAN TINGKAT PARTISIPASI ANGGOTA KELOMPOK TANI DENGAN DINAMIKA KELOMPOK TANI SERTA PENINGKATAN PRODUKSI PADI DI DESA CINTAMULYA KECAMATAN CANDIPURO KABUPATEN LAMPUNG SELATAN - Ahmad Miftahuddin; Dewangga Nikmatullah; Kordiyana K Rangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to examine participation level of farmer group members, farmer group dynamics, rice production increase, and the relationship between the the participation, group dynamics and rice production increase in Cintamulya Village, Candipuro District, South Lampung Regency.  Respondents in this study were 85 farmers. The study was conducted in August - September 2017.  The research method used was a survey method using a quantitative descriptive analysis method.  The relationship among variables are analyzed using nonparametric statistics Spearman rank correlation test.  The results showed that the participation rate of farmer group members is in a low category, group dynamics is in less dynamic category, and increase production is included in a low category.  There are significant relationships between the level of participation of members of farmer groups and farmer group dynamics, the level of participation and production increase, and group dynamics and production increase.  Key words: group dynamics, production increase, participation